Neologisms and their translation into Uzbek - Hamidov , Alisher (The Lingua Spectrum, 2024)
This paper explores the phenomenon of neologisms—newly coined words or expressions that emerge in a language to address contemporary needs, technologies, or cultural shifts. The focus is on the translation of these neologisms into Uzbek, examining the challenges and strategies involved in this process. The study highlights the importance of context, cultural nuances, and linguistic structures in effectively conveying the meaning of neologisms. Additionally, it discusses the role of technology and social media in the proliferation of neologisms and their impact on the Uzbek language. Through various examples, the paper aims to provide insights into how translators can navigate the complexities of neologism translation while preserving the intended meaning and relevance.